Cancer risk in patients with spondyloarthritis treated with TNF inhibitors: a collaborative study from the ARTIS and DANBIO registers. Issue 1 (4th May 2016) - Hellgren, Karin; Dreyer, Lene; Arkema, Elizabeth V; Glintborg, Bente; Jacobsson, Lennart T H; Kristensen, Lars-Erik; Feltelius, Nils; Hetland, Merete Lund; Askling, Johan
Abstract : Background: Safety data on cancer risks following tumour necrosis factor α inhibitors (TNFi) in patients with spondyloarthritis (SpA) (here defined as ankylosing spondylitis (AS), undifferentiated spondarthropaties (SpA UNS), psoriatic arthritis (PsA)) are scarce. Our objective was to assess risks for cancer overall and for common subtypes in patients with SpA treated with TNFi compared with TNFi-naïve patients with SpA and to the general population. Methods: From the Swedish (Anti-Rheumatic Therapy in Sweden (ARTIS)) and Danish (DANBIO) biologics registers, we assembled 8703 (ARTIS=5448, DANBIO=3255) patients with SpA initiating a first TNFi 2001–2011. From the Swedish National Patient and Population Registers we assembled a TNFi-naïve SpA cohort (n=28, 164) and a Swedish age-matched and sex-matched general population comparator cohort (n=131 687). We identified incident cancers by linkage with the nationwide Swedish and Danish Cancer Registers 2001–2011, and calculated age-standardised and sex-standardised incidence ratios as measures of relative risk (RR). Results: Based on 1188 cancers among the TNFi-naïve patients with SpA, RR of cancer overall was 1.1 (95% CI 1.0 to 1.2). Based on 147 cancers among TNFi initiators with SpA, RR versus TNFi-naïve was 0.8 (95% CI 0.7 to 1.0) and results were similar for AS and PsA when analysed separately. Site-specific cancer RRs: prostate 0.5 (95% CI 0.3 to 0.8), lung 0.6 (95% CI 0.3 to 1.3), colorectal 1.0 (95% CI 0.5 to 2.0), breast 1.3 (95% CI 0.9 to 2.0), lymphoma 0.8 (95% CI 0.4 to 1.8) and melanoma 1.4 (95% CI 0.7 to 2.6). Conclusions: In patients with SpA, treatment with TNFi was not associated with increased risks of cancer, neither overall nor for the six most common cancer types.